2007
DOI: 10.1021/pr0603710
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Pharmacodynamic Protein Markers of Centrally Active Drugs in Humans:  A Pilot Study in a Novel Clinical Model

Abstract: Recognizing specific protein changes in response to drug administration in humans has the potential for significant utility in clinical research. In spite of this, many methodological and practical questions related to assessing such changes are unanswered. We conducted a series of clinical studies to assess the feasibility of measuring changes in proteins related to drug administration using a mass-spectrometry proteomics technique capable of quantifying hundreds of proteins simultaneously in cerebrospinal fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 27 publications
1
8
1
Order By: Relevance
“…Nevertheless, prior to conducting the present clinical study, a methodological study absent of drug treatment had been performed to evaluate experimental techniques and identify possible sources of analytical, biological, and experimental variability that might occur during the assessment of analytes in the CSF (Patil et al 2007a). Analytical methods were established with quantitative dynamic ranges and limits of quantification for the anticipated endogenous concentrations of each analyte.…”
Section: Effects Of Ly2140023 Monohydrate and Ly404039 On Biogenic Ammentioning
confidence: 99%
“…Nevertheless, prior to conducting the present clinical study, a methodological study absent of drug treatment had been performed to evaluate experimental techniques and identify possible sources of analytical, biological, and experimental variability that might occur during the assessment of analytes in the CSF (Patil et al 2007a). Analytical methods were established with quantitative dynamic ranges and limits of quantification for the anticipated endogenous concentrations of each analyte.…”
Section: Effects Of Ly2140023 Monohydrate and Ly404039 On Biogenic Ammentioning
confidence: 99%
“…A clear understanding of proteomic variability under controlled conditions is crucial to enable future clinical studies to be appropriately designed and to improve the contextual interpretation of data obtained from pharmacoproteomic studies. It is also important to establish a suitable time period between drug administration and analysis primarily to allow sufficient time for a tissue-targeted drug to reach a pharmacokinetic steady state before exploring protein profile changes [36]. This is to ensure minimal interference from extraneous factors on endogenous variability, thus maximizing the probability of identifying even subtle drug-induced changes.…”
Section: Figurementioning
confidence: 99%
“…This is quite understandable as many other factors could determine the levels and activities of proteins such as regulated destruction of proteins. The results in our study shown indicated that the changes in protein levels were less than 100%, and the less than drastic changes in protein levels as observed have recently been found in a recent report on pharmacodynamic protein markers where the changes in protein levels fluctuated below 50% between the drug-administered individuals and the control individuals (Patil et al 2007). The identification of anabolic metabolic enzymes in S-enantiomer of propranolol-incubated cells was also in line with earlier clinical reports on the reversal of catabolism by propranolol treatment after severe burn (Herndon et al 2001), reduction of catabolism rate in patients receiving propranolol (Lamont et al 2000), and increase in body fat which is considered as one of the side effects of propranolol treatment (Lamont 1995).…”
Section: Enzymes Involved In Anabolism and Actin Polymerizationsupporting
confidence: 67%